P3.60 Factors associated to protected sex in youths. (8th July 2017) - Gutierrez, Eliana; Pinto, Valdir Monteiro; Elisabethb, Mariia; Lopes, M; Barros, Claudia Renata Santos; Basso, Caritas Relva
Abstract : Introduction: The study aimed to identify the factors associated with condom use during the last sexual intercourse. Methods: A population-based survey with youths aged 15–24, in São Paulo. The participants answered a questionnaire including knowledge and sexual behavioural data. Results: for 821 men and women the condom use during the last sexual intercourse was associated with: never having been married [adjusted prevalence ratio (PRadj ): 1.54 among men; 1.26 among women], having used a condom in the sexual onset (PRadj :1.23 among men; 1.54 among women), receiving condoms free of charge (PRadj :1.39 among men; 1.37 among women); besides, among men: casual sexual partner in the previous year (PRadj :1.24) and same-sex sexual partner (PRadj :1.23); among women with the sexual onset after 15yo (PRadj :1.25). HIV-testing has displayed a negative association for women (PRadj : 0.72). Conclusion: The condom is widely known, there is a pattern of it use during the first and last sexual intercourse; free condoms are important to improve it use by the youths, and people use condom as a risk management strategy. Condom as prevention strategy is still useful. After these results, the strategy of prevention was adopted as a public policy in the city of Sao Paulo: large condom dispensers were allocated in the 28 urban bus terminals, where 6 million people pass around daily and by the end of 2016, 80 million free condoms will be distributed.